Chinese Herbal Medicine Combined with Entecavir for HBeAg Positive Chronic Hepatitis B: Study Protocol for a Multi-Center, Double-Blind Randomized-Controlled Trial - Ye, Yong-an; Li, Xiao-ke; Zhou, Da-qiao; Chi, Xiao-ling; Li, Qin; Wang, Li; Lu, Bing-jiu; Mao, De-wen; Wu, Qi-kai; Wang, Xian-bo; Zhang, Ming-xiang; Xue, Jing-dong; et al. (Chinese journal of integrative medicine, 2018)
Background The domestic prevalence of chronic hepatitis B (CHB) in China is 7.18% in 2006, imposing great societal healthcare burdens. Nucleot(s)ide analogues (NUCs) anti-hepatitis B virus (HBV) therapies are widely applied despite the relatively low rate of seroconversion and high risk of drug-resistant mutation. More effective treatments for CHB deserve further explorations. Combined therapy of NUCs plus Chinese herbal medicine (CHM) is widely accepted in China, which is recognized as a prospective alternative approach. The study was primarily designed to confirm the hypothesis that Tiaogan-Yipi Granule (调肝益脾颗粒, TGYP) or Tiaogan-Jianpi-Jiedu Granule (调肝健脾解毒颗粒, TGJPJD) plus entecavir tablet (ETV) was superior over ETV monotherapy in enhancing HBeAg loss rate. Methods The study was a nationwide, large-scale, multi-center, double-blind, randomized, placebo-controlled trial with a designed duration of 108 weeks. A total of 16 hospitals and 596 eligible Chinese HBeAg positive CHB patients were enrolled from November 2012 to September 2013 and randomly allocated into 2 groups in 1:1 ratio via central randomization system: experimental group (EG) and control group (CG). Subjects in EG received CM formulae (TGYP or TGJPJD, 50 g per dose, twice daily) plus ETV tablet (or ETV placebo) 0.5 mg per day in the first 24 weeks (stage 1), and CHM granule plus ETV tablet (0.5 mg per day) from week 25 to 108 (stage 2). Subjects in CG received CHM Granule placebo plus ETV tablet (0.5 mg per day) for 108 weeks throughout the trial. The assessments of primary outcomes (HBV serum markers and HBV-DNA) were conducted by a third-party College of American Pathologists (CAP) qualified laboratory. Adverse effects were observed in the hospitals of recruitment. Discussion The study was designed to compare the curative effect of CM plus ETV and ETV monotherapy in respect of HBeAg loss, which is recognized by the European Association for the Study of the Liver as “a valuable endpoint”. We believe this trial could provide a reliable status for patients’ “journey” towards durable responses after treatment discontinuation. The trial was registered before recruitment on Chinese Clinical trial registry (No. ChiCTR-TRC-12002784, Version 1.0, 2015/12/23).